Overview of plant extracts as natural preservatives in meat - Mohammed Awad, Alzaidi; Kumar, Pavan; Ismail-Fitry, Mohammad Rashedi; Jusoh, Shokri; Ab Aziz, Muhamad Faris; Sazili, Awis Qurni (Wiley-Blackwell Publishing, 2022)
Plant extracts are obtained by extracting bioactive compounds from various plant sources such as leaves, seeds, fruits, roots, stems, and agro-industry byproducts. These are rich sources of bioactive molecules such as polyphenols (flavonols, anthocyanins, flavanols, benzoic acid, tannin, lignin, stilbenes, cinnamic acid, phenolic acids), terpenoids (carotenoids, terpenes, triterpenes, phytosterols, iridoids), organo-sulfurs, and alkaloids. These molecules exert antioxidant and antimicrobial effects; hence widely utilized as potential natural preservatives by partial or fully replacing the synthetic preservatives. Plants extracts could be used in cured and smoked meat products as nitrites/nitrates replacer by reducing residual nitrite, N-nitrosamine formation, and antimicrobial effect. The application of plant extracts by replacing synthetic additives helps in improving the functionality of meat products, the development of wellness foods or clean-label foods, and the production of healthier meat products without or with minimum use of synthetic additives. There should be a proper focus on using green, nontoxic solvents, exploring the novel, sustainable and economical source of bioactive compounds, efficient agro-industrial waste utilization, and novel environmentally friendly, sustainable green processing technologies to extract bioactive compounds from the plant source. The present review is intended to provide recent insights on technological aspects of extracting functional compounds from plant biomass and the utilization of these plant extracts as a potential alternative to synthetic preservatives in the meat matrix. Novelty impact statement: Plant extracts are rich sources of bioactive compounds exerting antioxidant, antimicrobial, and health-promoting activities. The application of plant extracts in the meat products would help in reducing the use of synthetic additives, replacer of nitrites/nitrates, production of wellness/healthier foods, and clean label foods. The applications of plant extracts are also successfully explored for developing active films for extending shelf life and quality preservation, preparation of intelligent pH strips for in situ quality monitoring, and use of various combinations of extracts with essential oils or even with a lower dose of antibiotics to reduce the risk of antibiotic resistance.